The profile of upper extremity muscular strength in female wheelchair basketball players: A pilot study - Külünkoglu, B.; Akkubak, Y.; Ergun, N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this study was to analyze and compare the profile of upper extremity muscle strength in female wheelchair basketball players with that of sex-matched non-disabled controls. METHODS: Nineteen female subjects were enrolled in this study. These were divided into two groups. Group 1 (N.=10) consisted of wheelchair basketball players and Group 2 (N.=9) of non-disabled individuals. Muscular strength in the shoulder was measured using an isokinetic dynamometer. Isometric and isotonic muscular endurance in the shoulder joint was evaluated in terms of the length of time subjects could hold a 5-kg dumbbell at 45° and the number of abduction repetitions to 45° with a 5-kg dumbbell in 30 seconds, respectively. Pinch strength and hand grip strength were measured using a Pinch gauge and hand dynamometer, respectively. RESULTS: Significant differences were observed between the groups in terms of all parameters of muscular strength in the shoulder joint, hand grip and pinch strength. Upper extremity muscular strength in female wheelchair basketball players was greater than in the non-disabled controls. CONCLUSIONS: We concluded that the difference in muscle strength between the groups mostly derived from using wheelchairs due to players` intense training and busy match schedules. Additionally, the profile of upper extremity muscle strength in female wheelchair basketball players in our study can be used as basic data for the introduction of exercise rehabilitation programs and as a guide for future research.